Les temporalités singulières de l’après-cancer pédiatrique.Résultats d’une recherche par les pairs - Bernard Chesa; Cécile Favre; Anne-Laure Foulques; Sabine Heinrich; Kai Yan Ly; Aurélie Pierre; Lionel Rivieri; Bénédicte Goussault; Agnès Dumas (Anthropologie & Santé)
This article reports on qualitative and participatory research on childhood cancer survivorship conducted in France by an association of former patients, Les Aguerris, in partnership with two sociologists. The interviews with 28 adult survivors of childhood cancer, collected and analyzed with the peer researchers, show that the experience of pediatric cancer unfolds in a succession of temporalities. The time of treatment, in childhood, and then the time after, until young adulthood, are first both marked by a form of silence around the disease, on both sides of the parent-child dyad. Thirty years later, comes the time for the late effects. From the awareness of the possible sequelae of cancer treatments to their sometimes-brutal experience, pediatric cancer is reintroduced into the biographical trajectory of concerned individuals, leading them to go through their history and redefine their identity several times, over the course of singular time sequences.